Preditores de mortalidade, análise espacial e estimativa dos gastos com vítimas fatais de atropelamentos em rodovias federais de Sergipe - Vaez, Andréia Centenaro (2016)
The traffic violence constitutes a serious public health problem, responsible for the deaths of thousands of young people in productive age. Among these victims, the pedestrians are part of the most vulnerable group and have the highest fatality rate. Goal: Conduct an ecological study of mortality associated with pedestrian accidents on federal highways in the state of Sergipe in the period 2009 to 2015. Method: Ecological study from the Information System on Mortality and the information system of the Federal Highway Police. It was built a model of logistic regression to determine the predictive factors associated with deaths caused by trampling, from the characteristics of the occurrence, the temporal aspects and the characteristics of the highway, vehicle, driver and pedestrian. The spatial analysis was performed using the TerraView 4.2.2 program, being used the intensity estimator Kernel, which generated a surface density for the visual detection of "hot areas" or hot spots of deaths from road kill after the maintenance of the track and coasting, urban land use, activity performed by the pedestrian, weather conditions and time of day. Results: There were 399 pedestrians injured in traffic accidents (ICD-10 V01 to V09), of which 146 was classified as fatal victims (49.1%), the majority were males (69.7%) aged up to 45 years (58.5%) and showed signs of drunkenness (9.3%). The multivariate analysis showed as a mortality predictor: the crossing of pedestrians on the highway (p=0.002), trampling in the rural area (p=0.003), and involvement of large vehicles (p =0.001). The spatial analysis showed the region of the Metropolitan area of Aracaju as epidemiological scenario of spatial risk with emphasis to the municipalities of Aracaju, São Cristóvão and Nossa Senhora do Socorro, concentrating the greater risk of death caused by trampling. The values spent were more than 62.3 million reais, being an average value per year of R$ 9.6million, of which more than 92% was related to the victim. Conclusion: We concluded that by combining different analysis techniques, the characteristics of the highway, vehicle and victim, it was highlighted the vulnerability of pedestrians to death in different areas of the highway. There is a need for extensive discussion for the elaboration of more effective public policies in reduction of mortality rates by trampling, through investments in highways, with improvements in shoulder engineering, installation of public lighting, walkways and medians, allowing the passage of pedestrians on highways. It is vital to intensify monitoring of speed limits and raise awareness of drivers regarding the legislation.